United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper estimates the long-run economic impact of Brexit on the United Kingdom under two distinct assumptions for the post-Brexit relationship between the United Kingdom and the European Union. These illustrative scenarios entail different degrees of higher trade costs, a more restricted European Union migration regime and reduced foreign inward investment. A standard multicountry and multisector computable general equilibrium model is used to quantify the impact of higher trade barriers. There is substantial sectoral heterogeneity in the impact, and regions with higher concentrations of the more affected sectors are likely to confront greater losses. The empirical analysis suggests the speed of sectoral labor relocation across sectors has been relatively low in the UK. Irrespective of these empirical estimates, policies, such as retraining, would be critical to facilitate faster adjustment of the economy to the post-Brexit equilibrium thereby helping to minimize the associated costs to individuals and in aggregate.